Symbiotic combination of Akkermansia muciniphila and inosine alleviates alcohol-induced liver injury by modulating gut dysbiosis and immune responses - Wei, Li; Pan, Yizhi; Guo, Yu; Zhu, Yin; Jin, Haoran; Gu, Yingying; Li, Chuanshuang; Wang, Yaqin; Lin, Jingjing; Chen, Yongping; Ke, Chunhai; Xu, Lanman (Frontiers in Microbiology, 2024)
Background Alcoholic liver disease (ALD) is exacerbated by disruptions in intestinal microecology and immune imbalances within the gut–liver axis. The present study assesses the therapeutic potential of combining Akkermansia muciniphila (A. muciniphila) with inosine in alleviating alcohol-induced liver injury. Methods Male C57BL/6 mice, subjected to a Lieber-DeCarli diet with 5% alcohol for 4 weeks, served as the alcoholic liver injury model. Various analyzes, including quantitative reverse transcription polymerase chain reaction (qRT-PCR), ELISA, immunochemistry, 16S rRNA gene sequencing, and flow cytometry, were employed to evaluate liver injury parameters, intestinal barrier function, microbiota composition, and immune responses. Results Compared to the model group, the A. muciniphila and inosine groups exhibited significantly decreased alanine aminotransferase, aspartate aminotransferase, and lipopolysaccharide (LPS) levels, reduced hepatic fat deposition and neutrophil infiltration, alleviated oxidative stress and inflammation, and increased expression of intestinal tight junction proteins (Claudin-1, Occludin, and ZO-1). These effects were further pronounced in the A. muciniphila and inosine combination group compared to individual treatments. While alcohol feeding induced intestinal dysbiosis and gut barrier disruption, the combined treatment reduced the abundance of harmful bacteria (Oscillibacter, Escherichia/Shigella, and Alistipes) induced by alcohol consumption, promoting the growth of butyrate-producing bacteria (Akkermansia, Lactobacillus, and Clostridium IV). Flow cytometry revealed that alcohol consumption reduced T regulatory (Treg) populations while increasing those of T-helper (Th) 1 and Th17, which were restored by A. muciniphila combined with inosine treatment. Moreover, A. muciniphila and inosine combination increased the expression levels of intestinal CD39, CD73, and adenosine A2A receptor (A2AR) along with enhanced proportions of CD4+CD39+Treg and CD4+CD73+Treg cells in the liver and spleen. The A2AR antagonist KW6002, blocked the beneficial effects of the A. muciniphila and inosine combination on liver injury in ALD mice. Conclusion This study reveals that the combination of A. muciniphila and inosine holds promise for ameliorating ALD by enhancing the gut ecosystem, improving intestinal barrier function, upregulating A2AR, CD73, and CD39 expression, modulating Treg cells functionality, and regulating the imbalance of Treg/Th17/Th1 cells, and these beneficial effects are partly A2AR-dependent.